Interventions in Gastric Varices: TIPS versus BRTO - Sanin, Emilio; Lopera, Jorge E.; de Assis, André Moreira; de Carvalho Melo Junior, José Andrade; Alvarez, Sergio (Digestive Disease Interventions, 2023)
Gastric varices (GV) are a relatively uncommon cause of bleeding in the gastrointestinal tract. Compared with esophageal varices (EV), GV have been less well studied and therefore there is less consensus on the best treatment alternative. GV have distinct hemodynamic and anatomic considerations which must be well understood to provide adequate treatments. The purpose of this review is to describe the endovascular treatment options available: transjugular intrahepatic portosystemic shunt and balloon-occluded retrograde transvenous obliteration (BRTO) and its variants. Each of these alternatives has its indications for different clinical scenarios. Both are effective in controlling acute bleeding, but BRTO seems to have better long-term results. A detailed description of indications, techniques, complications, and results is included.
Keywords: gastric varices; esophageal varices; transjugular intrahepatic portosystemic shunt; balloon retrograde transvenous obliteration